1993
DOI: 10.1177/089686089301300205
|View full text |Cite
|
Sign up to set email alerts
|

Cell Function and Viability in Glucose Polymer Peritoneal Dialysis Fluids

Abstract: Objective To investigate the biocompatibility profile of a new peritoneal dialysis fluid containing glucose polymer (GPF). Design Viability and function of peripheral neutrophils (PMN) from healthy donors and cultured human peritoneal mesothelial cells were assessed in vitro after exposure to dialysis fluids. Phagocytosis, leukotriene B4 synthesis, and respiratory burst activation were measured following stimulation with serum-treated zymosan (STZ) or opsonized Staphylococcus epidermidis (S. epidermidis). Bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2
6

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 21 publications
1
21
2
6
Order By: Relevance
“…This hypothesis is further supported by our observation (27) that M199 at pH 5.5, but not pH 6.5, significantly increased LDH release as compared with M199 at pH 7.4. Witowski et al (21) reported attenuated LDH release in response to lactate-buffered PD solutions with a pH adjusted to 7.4; however, Liberek et al (28) found that, in the presence of 0.1% fetal calf serum, mesothelial cell viability was reduced by both D and E, regardless of pH, when cells were exposed for 3 hours instead of the 1 hour used in the present study. Human monocyte viability was reduced by 7.5% glucose polymer in phosphate-buffered saline (PBS) at pH 7.4 to the same extent as by 1.36% glucose/ lactate solution at pH 5.5 (25).…”
Section: Discussioncontrasting
confidence: 54%
“…This hypothesis is further supported by our observation (27) that M199 at pH 5.5, but not pH 6.5, significantly increased LDH release as compared with M199 at pH 7.4. Witowski et al (21) reported attenuated LDH release in response to lactate-buffered PD solutions with a pH adjusted to 7.4; however, Liberek et al (28) found that, in the presence of 0.1% fetal calf serum, mesothelial cell viability was reduced by both D and E, regardless of pH, when cells were exposed for 3 hours instead of the 1 hour used in the present study. Human monocyte viability was reduced by 7.5% glucose polymer in phosphate-buffered saline (PBS) at pH 7.4 to the same extent as by 1.36% glucose/ lactate solution at pH 5.5 (25).…”
Section: Discussioncontrasting
confidence: 54%
“…Several in vitro and ex vivo studies have suggested that icodextrin may offer improved peritoneal membrane biocompatibility compared with conventional glucosebased dialysates by virtue of decreased glucose exposure, iso-osmolarity and reduced carbonyl stress. [30][31][32][33][34][35][36][37][38] Shortterm clinical studies involving generally small numbers of patients have demonstrated that dialytic small solute clearances and peritoneal transport characteristics remain well-preserved on icodextrin therapy for up to 24 months of follow up. 5,13,14,20,37,39,40 Moreover, a prospective, open-label, randomized controlled trial of 38 CCPD patients in two centres showed that dialysate effluent concentrations of a variety of peritoneal membrane markers (CA125, interleukin-8, carboxyterminal propeptide of type I procollagen and aminoterminal propeptide of type III procollagen) did not differ between glucose-and icodextrin-treated patients over a 2-year period.…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Several in vitro and ex vivo studies have suggested that icodextrin may offer improved peritoneal membrane biocompatibility compared with conventional glucose‐based dialysates by virtue of decreased glucose exposure, iso‐osmolarity and reduced carbonyl stress 30–38 . Short‐term clinical studies involving generally small numbers of patients have demonstrated that dialytic small solute clearances and peritoneal transport characteristics remain well‐preserved on icodextrin therapy for up to 24 months of follow up 5,13,14,20,37,39,40 .…”
Section: Biocompatibilitymentioning
confidence: 99%
“…The ultrafiltration capacity of a 7.5% icodextrin solution, used for the 8 hour -12-hour overnight dwell in continuous ambulatory peritoneal dialysis (CAPD) patients approximates to that of a 3.86% glucose solution (7). Iso-osmolar icodextrin may be potentially less damaging to the peritoneum and to peritoneal defense compared to the hyperosmolar (346 -486 mOsm/kg) glucose solutions currently used (8)(9)(10).…”
Section: ♦ ♦ ♦ ♦ ♦ Conclusionmentioning
confidence: 99%